2008
DOI: 10.1073/pnas.0707146105
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for orexins in emergence from general anesthesia

Abstract: The neural mechanisms through which the state of anesthesia arises and dissipates remain unknown. One common belief is that emergence from anesthesia is the inverse process of induction, brought about by elimination of anesthetic drugs from their CNS site(s) of action. Anesthetic-induced unconsciousness may result from specific interactions of anesthetics with the neural circuits regulating sleep and wakefulness. Orexinergic agonists and antagonists have the potential to alter the stability of the anesthetized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
281
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(300 citation statements)
references
References 37 publications
15
281
0
4
Order By: Relevance
“…Traditionally, this has been considered a pharmacokinetic phenomenon, but more recent data support the hypothesis that emergence from anesthesia is under distinct neurobiological control. [22][23][24] These findings bear on the present question. Even if we assume no difference in anesthetic sensitivity between demented and non-demented patients at the beginning of the anesthetic effect, there may nonetheless be significant differences at its end.…”
Section: Emergence From General Anesthesia Has Distinct Neurobiologysupporting
confidence: 57%
See 1 more Smart Citation
“…Traditionally, this has been considered a pharmacokinetic phenomenon, but more recent data support the hypothesis that emergence from anesthesia is under distinct neurobiological control. [22][23][24] These findings bear on the present question. Even if we assume no difference in anesthetic sensitivity between demented and non-demented patients at the beginning of the anesthetic effect, there may nonetheless be significant differences at its end.…”
Section: Emergence From General Anesthesia Has Distinct Neurobiologysupporting
confidence: 57%
“…Cela a été traditionnellement considéré comme étant un phénomène pharmacocinétique, mais des données plus récentes étayent l'hypothèse que l'émergence de l'anesthésie relève d'un contrôle neurobiologique distinct. [22][23][24] Ces constatations sont pertinentes pour la question présente. Même si nous supposons qu'il n'y a pas de différence de sensibilité aux anesthésiques entre les patients atteints de démence et les patients indemnes de MA au commencement de l'effet des anesthésiques, il pourrait néanmoins y avoir des différences significatives quand cet effet prend fin.…”
Section: L'émergence D'une Anesthésie Générale Répond à Des Caractériunclassified
“…administration of OXs reduced intravenous anesthesia time while OX1 receptor antagonist prolonged it [31,32]. Similarly, Kelts et al [33] reported that genetic ablation of OXergic neurons (OX/ataxin-3 mice) and selective OX1 receptor antagonists delayed emergence from volatile anesthesia such as sevoflurane and isoflurane. Based on these observations, sepsis-induced OXergic depression may reduce anesthesia requirement.…”
Section: Anesthetic Requirementmentioning
confidence: 94%
“…Despite advances made on the molecular action of various general anesthetics, such as their action on K + channels, GABA A , nicotinic and glutamate receptors (Franks, 2008), brain structures underlying general anesthesia remain unclear. Anesthetic-induced loss of consciousness was enhanced if arousal related brain structures were ablated or inactivated (Devor and Zalkind, 2001;Nelson et al, 2002;Flint et al, 2010;Franks, 2008;Kelz et al, 2008;Lu et al, 2008;Luo and Leung, 2009), and sleep deprivation increased the potency of propofol and isoflurane (Tung et al, 2002).…”
Section: Introductionmentioning
confidence: 99%